1985
DOI: 10.1172/jci112145
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 3 promotes the in vitro proliferation of murine pluripotent hematopoietic stem cells.

Abstract: Medium conditioned by activated T lymphocytes stimulates the in vitro proliferation of pluripotent hematopoietic stem cells

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

1987
1987
1989
1989

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 92 publications
(33 citation statements)
references
References 36 publications
1
31
0
Order By: Relevance
“…1). When either IL 3 at a concentration of 20 U/ml or the tumor promoter phorbol myristate acetate (PMA, 10-7 M) was added at the start of the incubation, the initial decline in total cell number was more marked over the first 24 h than in the control cultures (P < 0.001), but thereafter the number of cells per flask reached a plateau that remained constant for PMA for up to 144 h of culture; for IL 3, as we have previously reported (10), cell number began to increase after 96 h of culture.…”
Section: Resultssupporting
confidence: 54%
See 4 more Smart Citations
“…1). When either IL 3 at a concentration of 20 U/ml or the tumor promoter phorbol myristate acetate (PMA, 10-7 M) was added at the start of the incubation, the initial decline in total cell number was more marked over the first 24 h than in the control cultures (P < 0.001), but thereafter the number of cells per flask reached a plateau that remained constant for PMA for up to 144 h of culture; for IL 3, as we have previously reported (10), cell number began to increase after 96 h of culture.…”
Section: Resultssupporting
confidence: 54%
“…We have previously observed that under the culture conditions used, IL 3 promoted the in vitro proliferation of day 11 CFU-S only in the nonadherent population of the cultured marrow cells (10). When marrow cells cultured in the presence of 1-0 M PMA for 72 h were assayed separately for day 11 CFU-S as adherent and nonadherent cell populations, on average less than one colony per spleen was recovered from the adherent cell population, a frequency not different from that obtained for endogenous spleen colony formation.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations